The transformation of East Asian welfare states: the politics of welfare reform in South Korea - Lee, S (2012)
East Asian welfare states have experienced major reforms in the last two decades, raising the question as to whether these welfare reforms signify a fundamental departure from the East Asian welfare model, or merely an adaptation of the model to socioeconomic changes. Overshadowed by the state-driven policy-making model with a strong functionalist bias focusing on socio-economic drivers, the existing East Asian welfare state literature has overlooked the fundamental political change brought by the dual transition (i.e., democratisation and economic liberalisation), which have led to the emergence of pluralistic societies. In order to fill this gap in the literature, this thesis investigates the political underpinnings of welfare reforms in Korea with special attention to societal actors, (notably trade unions, employers’ associations, and political parties) whose role feature prominently in the comparative welfare state literature, are still largely neglected in East Asian welfare state research. Bringing these actors into the analysis, the thesis examines how the rise of societal actors has changed Korean welfare politics by constraining policy autonomy of the state in the domains of employment protection, unemployment protection, and work/family reconciliation policies. To this end, the thesis engages in analysing policy documents and in-depth elite interviews with senior government officials as well as high-profile representatives of employers associations, trade unions and parties. The thesis argues that the politics of the Korean welfare state has undergone a three step transformation process in the post-transition period. The developmental alliance could no longer function as the sole driving force of welfare state development during the first civilian government (1993-1998), when organised labour exercised its newly acquired status of a veto player. Furthermore, the old driving force of social policy-making, the developmental alliance, was replaced by the new alliance between the centre-left party and organised labour during the first left government (1998-2003) Lastly, parties moved to centre stage of social policy-making during the second left government (2003-2008) and the current conservative government (2008-presnet). Drawing on competing theories of the welfare state –in particular, the Power Resource approach, the employer-centred varieties of capitalism perspective, and the state-centred theorem, and the parties-matter thesis – the thesis contributes to developing a comprehensive political account on welfare state transformation in East Asia and to the better embedding of the East Asian welfare state literature into the comparative welfare state literature.